Phage susceptibility testing and infectious titer determination through wide-field lensless monitoring of phage plaque growth. - Prisca Perlemoine; Pierre R Marcoux; Emmanuel Picard; Emmanuel Hadji; Marc Zelsmann; Grégoire Mugnier; Aurélie Marchet; Grégory Resch; Larry O'Connell; Eric Lacot (PLoS ONE)
The growing number of drug-resistant bacterial infections worldwide is driving renewed interest in phage therapy. Based on the use of a personalized cocktail composed of highly specific bacterial viruses, this therapy relies on a range of tests on agar media to determine the most active phage on a given bacterial target (phage susceptibility testing), or to isolate new lytic phages from an environmental sample (enrichment of phage banks). However, these culture-based techniques are still solely interpreted through direct visual detection of plaques. The main objective of this work is to investigate computer-assisted methods in order to ease and accelerate diagnosis in phage therapy but also to study phage plaque growth kinetics. For this purpose, we designed a custom wide-field lensless imaging device, which allows continuous monitoring over a very large area sensor (3.3 cm2). Here we report bacterial susceptibility to Staphylococcus aureus phage in 3 hr and estimation of infectious titer in 8 hr 20 min. These are much shorter time-to-results than the 12 to 24 hours traditionally needed, since naked eye observation and counting of phage plaques is still the most widely used technique for susceptibility testing prior to phage therapy. Moreover, the continuous monitoring of the samples enables the study of plaque growth kinetics, which enables a deeper understanding of the interaction between phage and bacteria. Finally, thanks to the 4.3 μm resolution, we detect phage-resistant bacterial microcolonies of Klebsiella pneumoniae inside the boundaries of phage plaques and thus show that our prototype is also a suitable device to track phage resistance. Lensless imaging is therefore an all-in-one method that could easily be implemented in cost-effective and compact devices in phage laboratories to help with phage therapy diagnosis.